Association of Adherence to Specific Mediterranean Diet Components and Cardiorespiratory Fitness in Young Adults - Santi-Cano, Mª José (Nutrients, 2020)
Objective: Cardiorespiratory fitness (CRF) and a healthy diet may be part of an overall healthy lifestyle. The association between cardiorespiratory fitness and adherence to an overall Mediterranean Diet (MedD) pattern and specific MedD foods has been assessed. Design: Subjects completed a lifestyle survey and dietary pattern, using the validated MedD Adherence 14-item questionnaire and two self-reported 24-h dietary recalls. Participants’ height, body weight, waist circumference (WC), and CRF (maximum oxygen uptake, VO(2max,) ml/kg/min) were measured. Setting: University of Cádiz, Spain. Subjects: A sample of young adults (n = 275, 22.2 ± 6.3 years). Results: Mean VO(2max) was 43.9 mL/kg/min (SD 8.5 mL/kg/min). Most participants had healthy CRF (75.9%). The average MedD score was 6.2 points (SD 1.8 points). Participants who consumed more servings of nuts had higher VO(2max). Those who showed low CRF performed less physical activity (PA) and had a higher body mass index (BMI) and WC compared with those classified as having healthy CRF. Nut consumption was positively associated with VO(2max) (β = 0.320; 95% CI 2.4, 10.7; p < 0.002), adjusting for sex, age, smoking PA, BMI, WC, and energy intake, showing the subjects who consumed more nuts were fitter than young adults who consumed less. Conclusions: CRF is positively associated with nut consumption but not with the overall MedD pattern and all other MedD foods in the young adults. The subjects who consumed more servings of nuts were fitter than young adults who consumed less. Moreover, fitter subjects performed more PA and had a lower BMI and WC than those who had lower fitness levels.